3D CFD study of low-head direct chill slab casting of aluminium alloy AA3003. (2016) - Hasan, Mainul; Begum, Latifa
A 3D control volume-based finite difference model was developed to simulate an industrial scale low-head direct chill (DC) slab casting process for the intermediate freezing range aluminium alloy AA3003. The model took into account the coupled nature of the turbulent melt flow and solidification heat transfer aspect of the direct chill casting (DCC) process. The model was used to predict the velocity and temperature fields. By post-processing, the temperature results, the sump depth and the mushy thickness at the centre of the slab and the shell thickness at the exit of the mould were calculated. Specifically, three important process parameters, namely, casting speed, melt superheat and effective heat transfer coefficient at the metal-mould contact region were varied in the range of 60 to 180 mm/min, 16 to 64°C, and 1.0 to 4.0 kW/m²K, respectively. Consistent with the industrial practice, in the mould, in the impingement and the free streaming regions, a step-wise increase of the cooling water temperature was considered. The predicted results were then critically analysed and discussed.